Islam dan Budaya: Subtansi Nilai-nilai Pendidikan dalam Tradisi Islam Halal Bihalal - Enny Satria; Aziza Aryati (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Halal Bihalal is a cultural tradition rooted in Indonesian Islamic society, serving as a means to reconcile relationships, resolve conflicts, and restore social harmony after the fasting month of Ramadan. This practice reflects deeply embedded social and spiritual values that warrant academic exploration. Objective: This study aims to investigate the educational values embedded within the Islamic tradition of Halal Bihalal as practiced in Indonesian society. Method: The research employed the Systematic Literature Review (SLR) method. Relevant journal articles were gathered using the Google Scholar database. The SLR process consisted of four key stages: planning, conducting, analysis, and synthesis. Result: Findings revealed that the Halal Bihalal tradition encapsulates a wide array of educational values, including religiosity, honesty, tolerance, discipline, hard work, creativity, independence, patriotism, respect, friendliness, peacefulness, love of reading, environmental awareness, social care, and responsibility. Conclusion: The study concludes that Halal Bihalal in Indonesian society demonstrates consistent characteristics in terms of community opinions, implementation methods, food, attire, uniqueness, and underlying purpose. It affirms that this tradition is inherently embedded in Indonesian cultural identity. Contribution: This research contributes to the understanding of how local Islamic traditions like Halal Bihalal serve as rich sources of character education, and it highlights their potential integration into broader educational and cultural studies.